Return of post-pandemic face-to-face academic activities in the view of basic education students - Cardoso, Ana Gabriela Rodrigues (2022)
The present research aims to investigate the perception of basic education students about the return of in-person academic activities in the post-pandemic. With the field research through an online questionnaire, 155 students from eight public educational institutions from different municipalities located in the north and northeast regions of the country participated. The results show the student's desire to return to the face-to-face teaching format, 49% consider the learning "good" after returning, however, most still report difficulties related to this aspect. Thus, the research presents contributions to the educational area by evidencing students' perceptions about the educational situation they experience, contributing to the planning of actions that improve the teaching and learning process.